Data Science in Solar and Wind Energy Optimization: A Review - Mahjabeen, Farhana (Formosa Journal of Computer and Information Science, 2024)
This article explores the transformative role of artificial intelligence in optimizing solar and wind energy systems. Harvard researchers leverage extensive datasets and Microsoft Azure to analyze complex interactions between various signals, exceeding human capabilities. The article examines how AI enhances operational efficiency, stability, and sustainability of renewable energy systems, delving into fundamental AI applications and data science techniques. It further explores emerging trends like deploying advanced AI algorithms on energy grids. The research also analyzes the economic and environmental impacts of AI on renewable energy, addressing challenges such as economic barriers and regulatory frameworks. Finally, it discusses relevant regulations and standards for AI-powered renewable energy, considering diverse stakeholder perspectives